ШЛЯХИ ФОРМУВАННЯ У СТУДЕНТІВ МОТИВАЦІЇ ДО ПРОВЕДЕННЯ МОНІТОРИНГУ НАВЧАЛЬНИХ ДОСЯГНЕНЬ З МАТЕМАТИКИ - Горда, Ірина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті представлено модель проведення моніторингу навчальних досягнень студентів з математики у вищих аграрних навчальних закладах. Висвітлено результати експериментального дослідження особливостей взаємодії у системі «студент-викладач» під час проведення моніторингу навчальних досягнень студентів з математики. Зокрема, розглянуто деякі шляхи досягнення мети дослідження: формування зацікавленості та мотивації студентів в об’єктивних результатах моніторингових досліджень по визначенню рівня їх навчальних досягнень. В статье представлена модель проведения мониторинга учебных достижений студентов по математике в высших аграрных учебных заведениях. Представлены результаты экспериментального исследования особенностей взаимодействия в системе «студент-преподаватель» во время проведения мониторинга учебных достижений студентов по математике. В частности, рассмотрены некоторые пути достижения цели исследования: формирование заинтересованности и мотивации студентов в объективных результатах мониторинговых исследований по определению уровня их знаний. In the article the problem, which is connected with a need to measure and improve the quality of education in higher agrarian educational establishments, including mathematics, because mathematical disciplines are the basis for learning the most professional disciplines, forming qualitative general and professional training of students, is described. The development and implementation in higher agrarian educational establishments of monitoring system will help to solve this problem. The article presents the mathematical achievements monitoring model for students in higher agricultural education. The experimental studies results of the interaction in «student-teacher» during the monitoring of educational achievements of students in mathematics. We consider some ways to achieve the objectives of the study: the formation of interest and motivation of students in the objective results of the monitoring studies to determine the level of their knowledge’s.